Pergeseran Paradigma Pendidikan Dari Etis-Humanitis ke arah Pragmatis-Materialistik - Purbajati, Hafizh Idri (Sekolah Tinggi Islam Blambangan Banyuwangi, 2019)
Abstract To develop the potential as kholifah fii al-Ard, the methods used by each country and region are different. In Indonesia the potential development model used is set in the National Education System with tertiary level of education, from the level of kindergarten, elementary school to university as well as the inclusion of diplomas as proof of completing the level of education, as well as in other countries which is certainly adjusted with the character of the real conditions of the people. One implementation of the National Education System is the formation of educational institutions in order to make a conscious and planned effort to create an atmosphere of learning and learning process so that students actively develop their potential to have religious spiritual strength, self-control, personality, intelligence, noble character, and the skills required by themselves, the community, the nation and the state as an implementation of the mandate of the Constitution is to educate the nation's life. In its development, the influence of globalization and industry, as well as the development of science and information technology has a considerable influence on education, including the shifting of the educational paradigm from idealist-humanitis-ethical towards pragmatic-materealist in the midst of society. The method used is qualitative with a literature approach, as a knife analysis analyzes all information, sources, and documentation relating to education.